Vivências psicossociais de pacientes que concluíram o tratamento de tuberculose no interior do Estado de São Paulo: um estudo clínico-qualitativo - Dias, Ana Angélica Lima (2012)
Tuberculosis (TB) is a curable disease, however, is still a stigmatized disease. People with TB suffer from the disease, not only by clinical manifestations, but also with prejudice, embarrassing situations and even a self-discrimination that contribute to social isolation. This study aimed to analyze the psychosocial experiences of patients who were treated for TB in São Carlos - SP. A clinical-qualitative methodology was used as it seeks the meanings assigned by subject. 15 people who had completed TB treatment were studied as participants, the definition of the sample is given by the criteria of saturation. A data collection method, semi-directed interviews recorded on digital media were and were later transcribed and analyzed. Data analysis was based on the method of thematic content analysis as proposed by Bardin. Two thematic units were determined: Obstacles to cure TB and Psychosocial Experiences from the treatment. In the first thematic unit sub-categories that were listed: difficulties in diagnosis and supervised treatment. In the second thematic unity sub-categories that were listed: suffering in the face of disease, the impact on family and social context, the support of the health service and its effects after treatment. There is the thematic unity "obstacles to cure TB" that patients have difficulties in identifying the disease and health services sojourn until this diagnosis, patients suffer from adverse drug reactions; supervised treatment was identified as a facilitator for the completion of treatment, because they feel taken care of by the team and also as an obstacle to change the daily routine due to frequent displacement of health facilities. In the unit "Living resulting psychosocial treatment" found that the disease still causes distress to patients for fear of transmission, they are also victims of prejudice and fear of death. Suffering is also caused by stigmatizing, prejudicial actions in society. Family and health team offer support to patients and were essential to the completion of treatment. However, friends and colleagues keep away from them because of the fear of contagion and / or prejudice. The lack of knowledge about the disease and its mode of transmission are present in the statements of interviewees, which can still reproduce the stigma of the disease. The absence from work during treatment may be due to health conditions and also to minimize the constraints. It is concluded that health professionals should be aware of the repercussions that the treatment of TB leads the patient to minimize the obstacles that the disease causes in the patient's life. For this to happen the professional should allow sharing moments of anguish, suffering, psychosocial and biological changes so that the treatment is completed with fewer obstacles.